QUALITY CONTROL OF MAGNETIC FILLERS FOR MAGNETIC FORMULATIONS - Yu. Ya. Kharitonov; O. G. Cherkasova; S. P. Zavadskiy; S. N. Tsybusov; I. I. Krasnyuk (Jr); V. Yu. Grigorjeva (Разработка и регистрация лекарственных средств, 2019)
On the base of the experimental studies of some magnetic medications and dosage forms, magnetic fillers for magnetic dosage forms (by means of chemical, physical-chemical, physical methods) the experimental tests of the quality control of finely-dispersed magnetite, finely-dispersed barium ferrite have been developed.